Cegah Stunting dengan Peningkatan Pengetahuan Remaja Terkait Anemia Melalui Edukasi Kesehatan - Sinau, Ayu Tantri T.; Ramadhan, Kadar; Sakti, Putri Mulia (Poltekita: Jurnal Pengabdian Masyarakat, 2024)
Iron deficiency anemia is a common nutritional problem encountered among adolescents. Approximately 30% of the world's population, especially in developing countries, suffers from anemia. Adolescent girls are prone to iron deficiency anemia because they experience menstruation periodically, requiring additional iron to compensate for the blood loss during menstruation. Iron is needed for the production of hemoglobin in the body. The status of anemia can be determined through changes in hemoglobin levels. One effort to prevent anemia is by consuming Iron Supplement Tablets (IST). The purpose of this activity is to assess the level of knowledge among adolescent girls regarding anemia as an effort to prevent stunting. This activity involves not only lectures and question-and-answer sessions but also health education utilizing attractive promotional media such as posters related to anemia. The results of health education show that there is an increase in the level of knowledge among adolescent girls regarding anemia as an effort to prevent stunting before and after health education, from 66% to 100%. One tangible form of increased knowledge among adolescent girls is the routine consumption of iron supplement tablets (IST), one tablet per day during menstruation and one tablet per week when not menstruating.